Deciphering the origin of variation in the spin ground state and oxidation state of a Mn19 cluster on a Au(111) surface: is the Au(111) surface innocent?. Issue 57 (28th June 2019) - Nabi, Rizwan; Rajaraman, Gopalan
Abstract : Modeling the structure of a Mn19 cluster on an Au(111) surface reveals that exchange coupling constants vary grossly upon adsorption due to surface-induced structural distortions. This leads to significant variations in the ground state S values. Abstract : Periodic DFT calculations on a Mn19 cluster possessing S = 83/2 ground state and its reduced variant on a Au(111) surface unravel the importance of structural distortions that triggered drastic variations in the J values leading to a large reduction in the spin ground state. Reduction of Mn III ions leads to antiferromagnetic J s with a very small spin ground state manifesting the non-innocent behavior of the Au(111) surface.